Effectiveness of demand response in achieving supply-demand matching in a renewables dominated electricity system: A modelling approach. (September 2021) - Balasubramanian, S.; Balachandra, P.
Abstract: Globally, electricity systems are undergoing transitions from robust, carbon-intensive, and firm power conventional systems to uncertain, intermittent, and variable renewable energy integrated low carbon systems. These transitioning electricity systems have moved from a situation of "matching available supply with dynamic demand" to "matching dynamic supply with dynamic demand." These transformations have led to several new challenges - significant mismatch in periods of high supply and high demand, the shift in the method of accessing energy resources for electricity generation from "procure, store and generate when needed" to "generate when available, " continuous struggle to match variable supply with variable demand, and installed capacity redundancy, temporal as well as permanent leading to low plant load factors. Actions on the supply-side alone will not be enough to address these challenges and achieve optimal functioning of the electricity system. We need effective demand-side solutions, too, to manage variations in both supply and demand. In this paper, it is proposed to study the effectiveness of demand-side interventions as potential solutions for managing the variabilities introduced by renewable energy mainstreaming. Towards this, we develop a mixed-integer linear programming model to implement and validate emergency and economic demand response (DR) programs. DR options like load curtailment, short-, medium- and long-term load shifting are considered with both incentive-based and penalty-based pricing strategies to influence consumer participation. The Karnataka electricity system is used as a case study for model implementation and validation. The findings suggest that DR interventions are very effective in moderating variability in electricity demand by chopping the peak loads and topping the valleys. Further, benefits include postponement of installed capacity additions, enhanced utilization of available capacity, and minimization of demand variability. Highlights: Demand response for managing supply variations due to renewable energy integration. Studying effectiveness of DR in supply-demand matching using a modelling approach. Addressing supply variabilities using strategies from demand-side. Model is validated with a case study of renewable energy dominated system. Demand response is a win-win intervention for all the stakeholders.